2021
DOI: 10.3389/fpubh.2021.645739
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for SARS-CoV-2 Infection, Pneumonia, Intubation, and Death in Northeast Mexico

Abstract: Despite the social distancing and mobility restriction measures implemented for susceptible people around the world, infections and deaths due to COVID-19 continued to increase, even more so in the first months of 2021 in Mexico. Thus, it is necessary to find risk groups that can benefit from more aggressive preventive measures in a high-density population. This is a case-control study of suspected COVID-19 patients from Nuevo León, Mexico. Cases were: (1) COVID-19-positive patients and COVID-19-positive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
3
21
1
Order By: Relevance
“…Therefore, this was a lifestyle condition, which could be expected to predispose Mexican men to severe COVID-19. However, smoking was not positively associated in any of the analyses that we performed and the contrary phenomenon was observed, where smokers had a decreased probability of infection, severity, and death; this result has also been reported before [ 4 , 12 , 15 ]. An explanation for this could be that nicotine can have immunomodulatory and anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, this was a lifestyle condition, which could be expected to predispose Mexican men to severe COVID-19. However, smoking was not positively associated in any of the analyses that we performed and the contrary phenomenon was observed, where smokers had a decreased probability of infection, severity, and death; this result has also been reported before [ 4 , 12 , 15 ]. An explanation for this could be that nicotine can have immunomodulatory and anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 77%
“…Particularly, a recent study reported male sex, age, and comorbidities as risk factors for SARS-CoV-2 infection, pneumonia, intubation, and death in data collected from 11 February 2020 to 24 September 2020 with a total of 35,476 positive cases from a Mexican northeastern population [ 15 ]. By comparing periods of time analyzed by Hid-Cordero and colleagues (2021), the predominant SARS-CoV-2 variant was B.1, B.1.1, and B.1.1222, whereas, during the period studied in the present investigation, the predominant variants were delta (AY.20), followed by B.1.1.519.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In contrast, the associations of underlying medical conditions with infection acquisition are less well-defined, although retrospective reports have reported diabetes and obesity were associated with increased risk. 7,[19][20][21][22][23][24] Prospective studies have identified both demographic characteristics and comorbidities as risk factors associated with severe COVID-19. [25][26][27][28][29][30][31] Much of the data defining risk for either acquisition of SARS-CoV-2 or severe COVID-19 come from studies that relied on surveys, registries, or electronic medical records.…”
Section: Introductionmentioning
confidence: 99%
“…The first epidemiological and clinical investigations showed that most COVID-19 cases were attributed to elder or middle- aged men, with a mean incubation period of 5.2 days [ 7 , 8 ]. Aside from age and gender, there are also pre-existing conditions that are considered to be risk factors for SARS-CoV-2 infection, namely: hypertension, obesity, diabetes mellitus, asthma, chronic obstructive pulmonary disease, chronic kidney disease, smoking, and diseases that induce an immunosuppression state such as cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%